2017
DOI: 10.7150/jca.18685
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Invasion and Stromal S100A4 Expression at the Invasive Front of Colorectal Cancer are Novel Determinants and Tumor Prognostic Markers

Abstract: Object: The aim of the present study was to investigate the clinicopathological characteristics and prognostic factors associated with sporadic colorectal cancer (CRC). We examined the clinicopathological findings and immunohistochemical expression of tumor prognostic markers at tumor budding sites to determine their predictive value for patient prognosis.Materials and Methods: Immunohistochemical examination was performed by tissue microarray (TMA) of specimens from 106 patients with CRC. On hematoxylin and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Thus, we took RAS and BRAF mutations together to assess its predictive value. It showed no statistically significant relationship between the RAS/BRAF mutations and recurrence from surgical resection, but we observed that patients with vascular tumor thrombus had worse DFS than patients without vascular tumor thrombus which was consistent with previous findings [ 19 21 ]. Since ctDNA KRAS had a concordance of 81.25% compared with tumor tissue in our study, we further aimed to analyze the prognostic role of ctDNA gene mutation status in subsequent first-line palliative chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we took RAS and BRAF mutations together to assess its predictive value. It showed no statistically significant relationship between the RAS/BRAF mutations and recurrence from surgical resection, but we observed that patients with vascular tumor thrombus had worse DFS than patients without vascular tumor thrombus which was consistent with previous findings [ 19 21 ]. Since ctDNA KRAS had a concordance of 81.25% compared with tumor tissue in our study, we further aimed to analyze the prognostic role of ctDNA gene mutation status in subsequent first-line palliative chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…The most widely used marker for CAFs is α-SMA, a specific marker of myofibroblasts 11 - 13 . Additional markers for CAFs include CD10 28 , 29 , podoplanin 30 , FSP1 24 , 31 , and AEBP1; these markers are also thought to be associated with tumor invasion and metastasis 32 , 33 . In addition, EMT-related markers, including TWIST1 34 and ZEB1 35 , were also used in the present study because EMT-related proteins may also be markers of CAFs (e.g., co-expression of CAF- and EMT-related proteins is observed in the same fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EMT-related markers, including TWIST1 34 and ZEB1 35 , were also used in the present study because EMT-related proteins may also be markers of CAFs (e.g., co-expression of CAF- and EMT-related proteins is observed in the same fibroblasts). The antibodies we used in this study are widely available and are reliably and reproducibly used in studies of CRC 24 , 28 , 31 , 32 . Thus, these markers, i.e., α-SMA, CD10, podoplanin, FSP1, AEBP1, TWIST1, and ZEB1, are thought to be suitable for identifying the roles of CAFs and the EMT in SiCRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor invasion front is the area at the edge of the tumor which represents a critical interface at tumor progression and tumor cell dissemination (22). Changes in the environment of the tumor invasion front also affect the behavior of tumor cells and patient prognosis (23).…”
Section: Introductionmentioning
confidence: 99%